التنظيم الدستوري والقانوني لأسس مكافحة الفساد في ظل دستور جمهورية العراق 2005 - يونس مها بهجت (Journal of Legal Sciences, 2019)
Despite the differences of corruption from one place to another in the forms and the size of its spread and its impact on various aspects of life, is one of the most important causes of internal and external vulnerability of countries. Corruption in the jewel case Taatari disintegration of society as a result of loss of sovereignty core values, and the lack of respect for the law, and not to consecrate the concept of citizenship, and the absence of human rights and respect for the culture of the natural and spontaneous. Hence the need to make the problem of corruption and the outbreak in a major priority of the priorities of the state of society, since its devastating consequences on the political, social and economic aspects threaten the strength and position on the internal and international levels. So it shall work to promote the values of transparency and accountability in the legislation and strategy of the institutions, in order to spread the culture of anti-corruption and surround and consolidate the integrity between the various segments of society’s values. The anti-corruption on the foundations and principles of the President of the three are: integrity, transparency and accountability, and to investigate these grounds under the Constitution of the Republic of Iraq in 2005, it was first necessary to clarify the nature of corruption and that a statement on his concept, types and manifestations and stand on the causes of the spread of serious consequential effects, and exposure to the values and principles anti-corruption mechanisms achieved under the Constitution above, the centerpiece of our research is marked as "constitutional and legal regulation of the foundations of the fight against corruption under the Constitution of the Republic of Iraq for the year 2005".